Chagas disease prevention through improved housing using an ecosystem approach to health - Antonieta Rojas-
This Chagas disease prevention project via housing improvement aims to determine the efficiencyof different interventions in vector control. The following study describes the target communities, disease magnitude, and housing improvements. Transmission levels are analysed from an ecological and socioeconomic perspective. Special interest was focused on the peridomicile as the origin of domiciliary reinfestation. In the original project, three intervention programs were proposed, one for each of the three communities: (a) an insecticide spraying program; (b) a housing improvement program; and (c) a combined program of spraying and housing improvement. The three communities currently have different risks of exposure to triatominae reinfestation as a consequence of the type of intervention carried out. A new multidisciplinary approach which integrates participatory, community-based research and socioeconomic dimensions will allow to determine the efficiency of models for territorial ordering, community education, and environmental interventions in Chagas disease control.